Levantamento do padrão de consumo de tabaco e outras drogas na gestão de cuidados em saúde em assentamentos de uma comunidade rural - (:unkn) unknown (Universidade Federal de Goiás, 2015)
The increase in the indexes of use and misuse of tobacco and other drugs, both in Brazil and abroad, constitutes an effective reality. The constancy of social, psychological and biological damages arising from this use and their potential implications in health make up a global concern. Accordingly, this study had the objective of investigating the patterns of consumption of tobacco and other drugs in settlers of a rural community. We held an Integrative Review (IR) and, subsequently, a cross-sectional study in the Olga Benário settlement, located in the rural area of the municipality of Ipameri, Southeast Region of the State of Goiás. The target population was composed of 200 members of the 84 families over 18 years of age who lived in the settlement. The data were collected between September and November 2014. We used a semi-structured questionnaire and instruments such as Alcohol, Smoking and Substance Involvement Screening Test (ASSIST), Family APGAR and the Self-Report Questionnaire 20 (SRQ-20), which assessed the consumption of tobacco and other drugs, family functioning and screening of common mental suffering, respectively. The data were analyzed through the Stata Software Package, version 12.0. Prevalence indexes for consumption of substances were calculated with 95% confidence interval (95% CI). In order to estimate the factors associated with the consumption of tobacco and illicit drugs, we implemented multivariable models, thereby obtaining the prevalence ratio (PR) as an effect measure. The evidence of effectiveness of ASSIST was concentrated on the assistance in identifying and classifying psychoactive substances, in different audiences and age groups, and made up an effective instrument in Health Care. We have found high indexes of prevalence in patterns of tobacco consumption, and the associated factors were: higher age, low schooling level, evangelical religion, marijuana consumption, consumption of hypnotics and/or sedatives and male gender. Regarding the use of illicit drugs, the prevalence of lifetime use was significant in the surveyed individuals, with associated variables such as: male gender, tobacco consumption and disfunctionality in the family environment. The results of this study allowed us to confirm the use of psychoactive substances in the surveyed population, thereby corroborating the production of knowledge that subsidize health promotion actions and elaboration of health care policies for this population.
Standard lifting smoking and other drugs in health care management in setting of a rural community
Keywords: Gestão em saúde; Promoção da saúde; Drogas ilícitas; População rural; Transtornos relacionados ao uso de substâncias; Health management; Health promotion; Cross-sectional studies; Illicit drugs; Rural population; Disorders related to the use of substances; SAUDE COLETIVA::SAUDE PUBLICA